Investigating the Impact of Health Awareness on the Effectiveness of Preventive Health Measures - Ngyozie, Chyisom; Eniola, Nnena; Olumide, Dapo (Journal of Asian-african Focus in Health, 2024)
This study investigates the impact of focused health awareness on the effectiveness of preventive health measures in Nigeria. With the country grappling with a dual burden of infectious diseases and rising non-communicable diseases (NCDs), preventive healthcare strategies have become increasingly vital. Despite various interventions, including vaccination campaigns and health awareness programs, the role of awareness as a key factor in the success of these measures remains underexplored. The research employs a quantitative approach, using surveys to assess the awareness levels of Nigerian citizens regarding preventive health measures, and correlating these levels with the effectiveness of health interventions. A total of 400 respondents from urban and rural areas were surveyed to gauge their understanding of common health issues and their participation in preventive health programs. The results reveal that targeted health awareness programs significantly influence individuals' participation in preventive healthcare, with higher levels of awareness leading to better health outcomes. In particular, awareness regarding NCDs such as hypertension and diabetes was shown to have a stronger effect on health behaviors than awareness of infectious diseases like malaria. The study contributes to filling the gap in literature by providing empirical evidence on the importance of focused health awareness in improving the effectiveness of health interventions in Nigeria. The findings offer valuable implications for policymakers, healthcare practitioners, and development organizations, highlighting the need for tailored and context-sensitive health campaigns to optimize preventive healthcare strategies.